KOORDINASI BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN DAERAH (BP3D) KABUPATEN BOYOLALI DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH (RKPD) - Kunti Indira Murti (JI@P, 2021)
The research purpose was analyzed the coordination undertaken by the Badan Perencanaan Penelitian dan Pengambangan Daerah (BP3D) of Boyolali Regency in preparation of Regional Government Work Plan (RKPD). Research method used descriptive qualitative. Data collection techniques used interviews, observation, and documentation. Data analysis technique used Miles and Huberman intractive models. Validity data testing used triangulation techniques. Based on research results it can be concluded 1) The actions unity have been able to run well; 2) Communication has been going well that was carried out in the form of deliberations, coordination meetings, and Focus Group Discussions; 3) The division of work is very clear and reflects the ability of BP3D Boyolali Regency to work in a structured and planned manner; and 4) Discipline has been going well, this can be seen from the ability to complete the stages of RKPD preparation in accordance with a predetermined time frame.